Lucille Ball, the Queen of Show Business versus Lucy Ricardo, the Failed Actress - Aurélie Blot (Transatlantica)
Most American people, all generations taken into account, remember Lucille Ball as a great comic figure of the Fifties. Nonetheless, just a few people remember her as one of the most powerful women of her time. This might be because Lucille Ball refused to be considered as a businesswoman; she wanted to be seen as an actress above all. In this article, I will analyze how Lucille Ball became a businesswoman in spite of herself and how her success as an actress contributed to her success as a businesswoman.